1996
DOI: 10.1182/blood.v88.3.881.bloodjournal883881
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIIa and antithrombin III activity during severe sepsis and septic shock in neutropenic patients

Abstract: Septic shock and multiple organ failure may be associated with coagulation activation, disseminated fibrin formation, and consumption of coagulation inhibitors such as antithrombin III. We have evaluated prospectively coagulation measurements in patients with severe chemotherapy-induced neutropenia. This group of patients was chosen because of their high risk of developing severe septic complications, thus allowing serial prospective coagulation testing before and during evolving sepsis or septic shock. Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Although reduced activity of antithrombin is usually viewed as one of the diagnostic indicators of DIC (5,6), this ®nding is not speci®c to DIC in septic patients. The measurement of selected inhibitors of coagulation, including antithrombin and protein C, provide more useful prognostic information for these patients (3,4,13). This is the ®rst report to demonstrate that the markedly reduced plasma activity of antithrombin and protein C is not due to consumption coagulopathy in septic patients with DIC.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although reduced activity of antithrombin is usually viewed as one of the diagnostic indicators of DIC (5,6), this ®nding is not speci®c to DIC in septic patients. The measurement of selected inhibitors of coagulation, including antithrombin and protein C, provide more useful prognostic information for these patients (3,4,13). This is the ®rst report to demonstrate that the markedly reduced plasma activity of antithrombin and protein C is not due to consumption coagulopathy in septic patients with DIC.…”
Section: Discussionmentioning
confidence: 80%
“…Sepsis is another important underlying disease responsible for DIC, and the most striking reduction in plasma antithrombin activity is often observed in septic patients with DIC (12,13). In this paper, we have attempted to clarify the etiology of this reduced antithrombin activity in septic patients with DIC, speci®cally investigating whether the decrease in plasma antithrombin activity is due to consumption coagulopathy.…”
mentioning
confidence: 99%
“…DIC is characterized by reduced levels of endogenous coagulation inhibitors such as antithrombin (AT). A previous study suggested that marked reductions in serum AT levels are associated with unfavorable outcomes in septic patients [8]. Therefore, therapeutic supplementation of AT was suggested for severe sepsis and septic shock in the 1990s [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest that in the present study FVIIa levels rose in parallel with levels of TF. One would expect FVIIa to decrease due to the formation of the FVIIa-TF complex, as seen in sepsis [18,19]. Of relevance, Kondo et al [20] found the FVIIa-TF complex to be inhibited by a placental anticoagulant protein.…”
Section: Discussionmentioning
confidence: 99%